Back Cover: Thermal Decomposition Enhancement of HMX by Bonding with TiO2 Nanoparticles (Prop., Explos., Pyrotech. 4/2019). Issue 4 (2nd April 2019) - Zhu, Qing; Xiao, Chun; Xie, Xiao; Zheng, Bao‐hui; Li, Shang‐bin; Luo, Guan
Abstract : The cover picture shows the comparing combustion performance of the original HMX and the bioinspired composite HMX@PDA@TiO2  . The mussels in the sea represent the bioinspired fabrication method for the composite in the paper. The hollow bubbles are polydopamine film and dopamine molecular in solution with different pH values. The yellow particles represent the nanocatalysts TiO2 anchored via bonding on the surface of HMX. The picture reveals that the interaction properties of the composite greatly influence the composite performance. Details are discussed in the articles by Q. Zhu et al. on page 438 ff.